Features of Medical Care Providing to Patients with Digestive Diseases in the Krasnodar Region during the COVID-19 Pandemic - N. V. Korochanskaya; V. M. Durleshter; S. A. Gabriel; O. V. Kovalevskaya; S. N. Serikova; M. A. Basenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
The aim of the study: optimization the medical care provision to patients with diseases of the digestive system (DD) in the Krasnodar Region during the COVID-19 pandemic.Material and methods. The analysis of the features of the DD course in the Krasnodar Region was carried out according to the data of form C 51 “Distribution of the dead by sex, age groups and causes of death” of the Territorial Federal State Statistics Service in the Krasnodar Region, as well as monitoring the quality of medical care for patients with DD for the period from 2019 to 2021 years.Results. During the COVID-19 pandemic, the routing of gastroenterological patients, dispensary observation and preventive measures have undergone some changes. In the structure of total mortality in the Krasnodar Region, mortality from DD was 21.6 % in 2020 and 4.0 % in 2021. The decrease in the growth of mortality rate, including from DD, in the second year of the pandemic is associated with the completed healthcare systems reformatting. The increase in hospital mortality in patients with gastric and duodenal ulcers, ulcerative colitis, and diverticular disease had a significant impact on mortality rates from DD. The decreasing number of hospitalizations was explained due to the conversion of a number of hospitals into hospitals for the treatment of patients with COVID-19. The hospitalization was mainly carried out for emergency indications and patients with a more severe course of the disease. The pandemic has increased the need for telemedicine: 378 tele-consultations on the gastroenterological profile was carried out in the Krasnodar Region in 2021.Conclusion. Healthcare system workload in the Krasnodar Region increased significantly during the coronavirus pandemic that required a number of structural adjustments. In recent times, the regional health care is returning to the planned mode of providing medical care.